Adolescents' multiple versus single primary attachment figures, reorganization of attachment hierarchy, and adjustments: the important people interview approach. Issue 5 (3rd September 2018) - Umemura, Tomotaka; Lacinová, Lenka; Kraus, Jakub; Horská, Eliška; Pivodová, Lenka
ABSTRACT: Using 212 adolescents from a central-European country (mean age = 14.02, SD = 2.05, ranged from 11 to 18 years; females = 54%) and a multi-informant method to measure adolescents' behavioral and emotional adjustments, the present study explored three aspects regarding the attachment hierarchy. (1) The three types of behavioral systems of Rosenthal and Kobak's important people interview (IPI) were initially validated using an exploratory factor analysis with a US sample. Using a confirmatory factor analysis with a Czech sample, we replicated these three behavioral systems: attachment bond, support seeking, and affiliation . (2) We found that adolescents who developed attachment bond to multiple primary attachment figures were likely to score lower on both teacher-rated and parent-rated internalizing problems compared to those who had a single primary attachment figure. These multiple primary attachment figures tended to be family members (not peers). (3) Early adolescents who placed parents low in their attachment hierarchy scored higher on self-reported negative affect and lower on self-reported positive affect compared to early adolescents who placed parents high. The present study highlights multiple (vs. single) primary attachment figures as a protective factor and the premature reorganization of attachment hierarchy as a risk factor for adolescents' emotional and affective adjustments.